Effects of initial soil moisture content on soil water and nitrogen transport under muddy water film hole infiltration - Liu, Lihua; Fei, Liangjun; Chen, Lin; Hao, Kun; Zhang, Quanju (International Journal of Agricultural and Biological Engineering, 2021)
Film hole irrigation has been widely adopted as an effective water-saving irrigation technology in the arid and semiarid areas of China. To investigate the effects of initial soil moisture content (θ0) on soil water and nitrogen transport characteristics under muddy water film hole infiltration, the laboratory experiments were conducted with muddy water film hole infiltration, using five initial soil moisture content treatments. The models for describing the relationships between the cumulative infiltration (I(t)) and infiltration duration (t); the relationship among the horizontal and vertical migration distances of the wetting front (Fx, Fz), θ0 and t, were established. The results showed that the initial soil moisture content had a significant effect on I(t), Fx, Fz and moisture content distribution in the wetted body. The change of I(t) over t conformed to Kostiakov model. With the increase of θ0, the infiltration coefficient (K) gradually decreased. NO–3-N was mainly distributed in the range of the wetting radius of 15 cm, while NH +4-N was mainly distributed in the range of the wetting radius of 8 cm. This study can provide a theoretical basis and technical support for film hole irrigation.Keywords: film hole irrigation, muddy water, initial soil moisture content, water and nitrogen transport, water redistributionDOI: 10.25165/j.ijabe.20211404.6024Citation: Liu L H, Fei L J, Chen L, Hao K, Zhang Q J. Effects of initial soil moisture content on soil water and nitrogen transport under muddy water film hole infiltration. Int J Agric & Biol Eng, 2021; 14(4): 182–189.